E-044 Patient outcomes after treatment of brain aneurysm in small diameter vessels with the silk vista baby flow diverter: a systematic review. (23rd July 2022) - Hanel, R; Cortez, G; Benalia, V; Sheffels, E; Sutphin, D; Pederson, J; Pereira, V
Abstract : Background: Initial technical constraints on the treatment of aneurysms in small parent vessels using flow diverters included challenges in navigating the delivery system and catheter size compatibility, as well as unavailability of smaller devices. The Silk Vista Baby (SVB, BALT) is a first-in-class flow-diverter device delivered using a 0.017' microcatheter, designed for the treatment of intracranial aneurysms, including those in small diameter vessels. A systematic literature review (SLR) of the literature was performed to evaluate the safety and efficacy of using SVB to treat intracranial aneurysms in vessels less than 3.5 mm in diameter. Methods: We performed a PRISMA-compliant SLR to evaluate the outcomes of SVB in the treatment of aneurysms in small intracranial vessels. Primary outcomes were occlusion status and major stroke, and secondary outcomes included all-cause mortality, procedure-related neurologic death, and post-operative aneurysm rupture. Data were expressed as descriptive statistics only. Results: A total of four studies, including 163 patients with 173 intracranial aneurysms, were included. The most common aneurysm locations were the anterior cerebral artery (24.9% [43/173]), the middle cerebral artery (24.3% [42/173]), and the anterior communicating artery (23.1% [40/173]). Parent artery diameter ranged from 0.9 mm to 3.6 mm, most aneurysms were saccular (81.8%), and 29% were acutely or previously ruptured. Overall, 32.9% (57/173) of the aneurysms managed with the SVB had previously been treated, mainly using coiling. Moreover, adjunct coiling use ranged from 2.1% to 30.2%. Technical success was obtained in 98.8% of cases. Overall, complete and adequate (complete and near-complete) aneurysm occlusion were 60.6% and 72.1%, respectively, on studies with available early-term follow-up (mean ≥6 months). Postoperative bleeding rate across the studies was 1.8%, all case occurring previously or acutely ruptured aneurysms. Major stroke was noted in 1.2% of cases, and branch occlusion or stent thrombus formation in 5.5%. Mortality rate among the studies was 2.5%, with 3 instances adjudicated as neurologic deaths (1.8%). Conclusion: This systematic review suggests that SVB is a safe and effective treatment for intracranial aneurysms in small vessels. Device trackability and reduced system dimensions, also facilitated the treatment of previously judged not amenable lesions, including a wide range of aneurysms located in anterior and posterior circulation distal vessels. Further prospective and comparative studies with patient outcome data specific to aneurysm location are needed to confirm the safety and efficacy of SVB. Disclosures: R. Hanel: 1; C; Unrestricted research grant from NIH, Interline Endowment, Microvention, Stryker, CNX.. 2; C; Medtronic, Stryker, Cerenovous, Microvention, Balt, Phenox, Rapid Medical, and Q'Apel. He is on advisory board for MiVI, eLum, Three Rivers, Shape Medical and Corindus.. 4; C; InNeuroCo, Cerebrotech, eLum, Endostream, Three Rivers Medical Inc, Scientia, RisT, BlinkTBI, and Corindus.. G. Cortez: None. V. Benalia: None. E. Sheffels: None. D. Sutphin: None. J. Pederson: None. V. Pereira: None.